Perception of caregivers of persons with schizophrenia about a health education program - Lomeo, Roselane (2018)
The mental health policy of Brazil has been guided by the search for citizenship, social equality and autonomy of the individuals with mental disorders and it started with the deinstitutionalization process. On the other hand, this paradigm shift contributed to making the patients stay in the family environment and thus the need for family members to play the role of caregivers. The attributions of these care functions have contributed to a physical and emotional overload. Using a psychoeducational approach focused on the family member/caregiver of people with schizophrenia, this study proposed to check the caregivers' perception about the importance of the practice of relaxation activities for the promotion of selfcare. The intervention was performed during a six-month period. Participants were 31 family caregivers of mental health cohabitation centers in the city of Belo Horizonte, Brazil. Using the relatives’ reports about the perception of the intervention, categories were listed and treated with the support of the software webQDA. The results revealed through the family members' perception, that the intervention program provided them with contributions such as wellbeing, self-control over impulses, increased self-esteem, and encouragement for self-care. The literature reinforces that the educational practice in health is composed of educational activities aimed at the development of individual and collective capacities aimed at improving the health and quality of life of people. The intervention program with relaxation exercises contributed to an improved physical and mental health for family caregivers, awakening them to self-care